Impact of the COVID-19 Pandemic on Changing the Content of Social Media Advertising - Seberíni, Andrea; Tokovska, Miroslava (Studia Ecologiae et Bioethicae, 2021)
Social media and advertising offers opportunities for receiving pre- and post-purchase information. Advertising plays a significant role in business marketing, as every company wants its product to be successful, and familiar to its target audience, and thus, it is essential to promote it. Promotion plays an important role within the marketing mix, as its aim is to draw the attention of potential buyers. The main purpose of this study is to find out how social media, especially advertising, changed its content during the COVID-19 pandemic. A questionnaire was distributed among respondents by means of social media. This way we included representatives of each age category trying to resemble, as closely as possible, the Slovak market. From among the randomly selected participants (social media users), 135 respondents completed the questionnaire. As for the impact of the COVID-19 pandemic, in terms of advertising, we found out that there had been a certain change. According to the answers of our respondents, the changes related to the content of advertisements, the motives used, their narratives, offered products or services, or the combination of all the above. Consumers noticed an increased amount of COVID-19 related products such as face masks, disinfectants, etc.